Innovation of Coffee Bali : from Aromatherapy to Immune Booster - Ida Ayu Adi Trisnawathi (Bali Tourism Journal, 2021)
Balinese Coffee might sound unfamiliar since it is a new player in the premium gourmet world. Bringing a rich aroma and distinctive smoky taste, it has attracted coffee connoisseurs to feel at home on vacation in Bali. Thanks to the mineral-rich volcanic soil, practices involving natural fertilizers and plantings method according to the Tri Hita Karana concept. Coffee has a distinctive flavors to hook its audience, creating many coffee-drinking cultures in most countries, including Indonesia. Coffee can be consumed as a beverage or processed into other products without reducing its high selling value. Many innovations to turn coffee beans into perfume, aromatherapy, and coffee bean accessories have been highly-demanded. Taking advantage of the uprising prestige of coffee, the Governor of Bali Wayan Koster also proposed an idea that herbal drink experts doubted, namely mixing Coffee with Balinese arak. However, expert doubted the Governor’s proposal and advised the public to look for other herbal drinks references.